Sistem Keamanan Perumahan Menggunakan Face Recognition - Desi Ramayanti; Yuwan Jumaryadi; Daim Muhammad Gufron; Dio Dava Ramadha (TIN: Terapan Informatika Nusantara, 2023)
The residential environment system is a system that can be used to assist security officers and neighborhood residents to carry out environmental monitoring of crimes both coming from outside the environment and from the environment itself. This residential security system application uses the face recognition method carried out by residential security. The security system is an important point, which makes it the most important goal of researchers. Data collection methods used such as, observation, observation and literature study. The results of this study are to create a security system application using android-based facial recognition. The conclusion of this research is that this residential security system application is designed with simple systems and features to make it easier for users or users, with the Face Recognition method it makes it easier for security guards to carry out security for people who come out of housing, and the security system application is an application designed to help community and security officers so as not to lose the motorized vehicles of residential residents